THE USE OF SECONDARY RESOURCES OF FRUIT RAW MATERIAL IN TECHNOLOGY OF CONFECTIONERY AND BAKERY PRODUCTS - Bakin I.A.; Mustafina A.S.; Vechtomova E.A.; Kolbina A.Yu. (Техника и технология пищевых производств)
The results of research on improving the technology of flour confectionery and bakery products enriched with components of secondary resources of fruit raw material to increase their nutritional value are given in the article. The purpose of the study is to substantiate the production of flour confectionery and bakery products with increased nutritional value when using secondary resources of fruit raw material on the basis of studies of quality indices of semi-finished and finished products. Different samples of secondary fruit raw material in the form of cake and meal have been analyzed. A secondary product is obtained after pressing the berries or after the extraction with water and water-alcohol solvents. It is suggested to dry up secondary products in the form of cake and meal in the convective dryer at the temperature of 40°C to the humidity of 20 % to improve their technological properties. The possibility of adding extra raw material into the dough for producing butter biscuits and bakery goods has been studied. It has been established that consumer characteristics of bakery goods with added dried-up blackcurrant cake are worse than those of check samples. By results of research it has been determined that introduction of the dried-up cake of blackcurrant berries into dough for producing butter biscuits doesn't influence its properties and physical and chemical properties of a finished product. It has been found that the optimum dosage of the additive is 15% of the flour mass which doesn't lead to the worsening of organoleptic factors of finished products. The data on the analysis of the chemical composition of butter biscuits with added cake of blackcurrant berries ispresented. It has been found that the content of food fiber in the product increases by 33.5% compared to the check sample. Produced biscuits are enriched with trace elements and mineral substances (ferrum, potassium, calcium, magnesium, chlorine), P-active substances and antotsiana. Experimental and calculated data prove the possibility of using the cake of blackcurrant berries for the production of butter biscuits with increased nutritional value.